Transition Metals and Sulfur - A Strong Relationship for Life - Kroneck, Peter; Kroneck, Peter; Sosa Torres, Martha; Sosa Torres, Martha (Metal Ions in Life Sciences ;, 2020)
Metal-Sulfur clusters play an essential role in living organisms through the unique character of sulfur-metal bonding. The new volume in prestigious Metal Ions in Life Sciences explores different transition metal complexes with sulfur, their biosynthesis and biological functions in regulation of gene expression, catalysis of important metabolic reactions and protein structure arrangement.